The effect of vitamin D supplementation on oxidative stress and inflammatory biomarkers in pregnant women: a systematic review and meta-analysis of clinical trials - Soudabe Motamed; Bahareh Nikooyeh; Razieh Anari; Somayeh Motamed; Zeinab Mokhtari; Tirang Neyestani (BMC, 2022)
Abstract Background Vitamin D deficiency, a common problem among pregnant women, is linked with maternal inflammation, oxidative stress and consequent adverse pregnancy outcomes. The aim of this systematic review was to evaluate the effect of vitamin D supplementation on oxidative stress and inflammatory biomarkers in pregnant women according to the PRISMA guidance. Methods Four databases including PubMed/MEDLINE, Scopus, Web of Science and Cochrane were used for searching papers published until 25th July 2022. Clinical trials that assessed 25-Hydroxyvitamin D (25(OH)D), inflammatory markers (including high sensitivity C-reactive protein (hs-CRP) and certain cytokines) and oxidative stress markers (including malondialdehyde (MDA), total antioxidant capacity (TAC) and glutathione (GSH)) in pregnant women, were included in this review. The primary search of three databases displayed 21571 records. After removing duplicates and irrelevant articles, 17 eligible RCTs included for more evaluation. Random effect model and Der Simonian-Laird method were used to pool the data of studies. Risk of bias assessed according to version 2 of the Cochrane risk-of-bias tool for randomized trials. Results According to the meta-analysis result, vitamin D supplementation caused a significant increase in the maternal circulating concentrations of 25(OH)D (SMD 2.07; 95%, CI 1.51, 2.63; p < 0.001), TAC (SMD 2.13, 95% CI 1.04 to 3.23, p < 0.001) and GSH (SMD 4.37, 95% CI 2.9 to 5.74, p < 0.001) as well as a significant decrease in the levels of MDA (SMD -0.46, 95% CI -0.87 to -0.05, p = 0.02). However, it had no significant impact on hs-CRP concentrations (SMD 0.24; 95% CI, -0.55, 1.03; p = 0.50). Conclusion In the present study, vitamin D supplementation led to increased levels of 25(OH)D, TAC and GSH and also decreased concentration of MDA. Nevertheless, because of low certainty of evidence, these findings have to be declared conservatively. Trial registration Registration code in PROSPERO website: CRD42020202600